Microscopic analysis of high lithium-ion conducting glass-ceramic sulfides - Park, M.; Jung, W.D.; Choi, S.; Son, K.; Jung, H.-G.; Kim, B.-K.; Lee, H.-W.; Lee, J.-H.; Kim, H. (Korean Ceramic Society, 2016)
We explore the crystalline structure and phase transition of lithium thiophosphate (Li7P3S11) solid electrolyte using electron microscopy and X-ray diffraction. The glass-like Li7P3S11 powder is prepared by the high-energy mechanical milling process. According to the energy dispersive X-ray spectroscopy (EDS) and selected area diffraction (SAD) analysis, the glass powder shows chemical homogeneity without noticeable contrast variation at any specific spot in the specimen and amorphous SAD ring patterns. Upon heating up to 260°C the glass Li7P3S11 powder becomes crystallized, clearly representing crystal plane diffraction contrast in the high-resolution transmission electron microscopy image. We further confirm that each diffraction spot precisely corresponds to the diffraction from a particular Li7P3S11 crystallographic structure, which is also in good agreement with the previous X-ray diffraction results. We expect that the microscopic analysis with EDS and SAD patterns would permit a new approach to study in the atomic scale of other lithium ion conducting sulfides.
Keywords: Chemical analysis; Electrolytes; Electron microscopy; Energy dispersive spectroscopy; Glass; Glass ceramics; Ions; Lithium; Lithium alloys; Lithium compounds; Lithium-ion batteries; Mechanical alloying; Metallography; Milling (machining); Phase transitions; Solid electrolytes; Solid state devices; Sulfur compounds; Transmission electron microscopy; X ray diffraction; X ray spectroscopy; All-solid state batteries; Crystalline structure; Crystallographic structure; Energy dispersive X ray spectroscopy; High-energy mechanical milling; Lithium ion conductors; Microscopic analysis; Selected area diffraction; High resolution transmission electron microscopy